BS EN ISO 13844. Plastics piping systems. Elastomeric-sealing-ring-type socket joints for use with plastic pressure pipes. Test method for leak tightness under negative pressure, angular deflection and deformation. (11th August 2021) - British Standards Institution,
No abstract available